ANALISIS PENGARUH CAMPURAN LIMBAH PLASTIK LOW DENSITY POLYETHYLENE DAN FLY ASH TERHADAP DENSITAS, KUAT TEKAN DAN KONDUKTIVITAS TERMAL SEBAGAI BAHAN ALTERNATIF BATAKO - Dzal Aidi Al Ayyubi; Fadhli Dzil Ikram (Jurnal GEAR (Energi, Perancangan, Manufaktur & Material), 2023)
The availability of energy, including electrical energy, is dwindling and most of the energy used comes from non-renewable energy in decreasing amounts. In addition to the availability of energy, global warming is also a problem for the whole world. Greenhouse gas emissions are the main cause of global warming. Various types of human activities can also increase gas emissions, one of which is the use of electrical energy. The use of AC or air conditioner is an electronic device that requires a lot of electrical energy. To minimize the use of air conditioning, we need bricks that have a low thermal conductivity value but are still light and strong. Utilization of waste is something that is still rarely done. Some types of waste that are rarely used are LDPE plastic waste and fly ash. Both of these wastes have characteristics that are very suitable to be used as alternative raw materials in making bricks. The purpose of this study was to determine the value of density, compressive strength and thermal conductivity as well as the quality produced by brick made from LDPE plastic and fly ash. The research was carried out by melting LDPE plastic and then mixing it with fly ash until smooth to be printed and testing for density, compressive strength and thermal conductivity. From the research results obtained the best data for density 1.265g/cm3, compressive strength 28.6518 MPa and thermal conductivity 1.427 W/mK.